1995
DOI: 10.1074/jbc.270.17.10231
|View full text |Cite
|
Sign up to set email alerts
|

Alternately Spliced NH2-terminal Immunoglobulin-like Loop I in the Ectodomain of the Fibroblast Growth Factor (FGF) Receptor 1 Lowers Affinity for both Heparin and FGF-1

Abstract: Alternate splicing of a single exon encoding an NH2-terminal immunoglobulin (Ig) disulfide loop in the ectodomain of the fibroblast growth factor receptor (FGFR) types 1 and 2 results in alpha and beta isoforms that exhibit 3- and 2-Ig loops, respectively. Previously we demonstrated that alternately spliced Loop I has no independent ligand binding activity but is sufficiently interactive with the ligand- and heparin-binding site formed by Loops II and III to lower affinity for the same fibroblast growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
106
2
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 11 publications
3
106
2
2
Order By: Relevance
“…Binding of heparin to the canyon stabilizes the dimeric structure of the FGF⅐FGFR complex. This hypothesis is consistent with the results of previous studies demonstrating that FGFR1 lacking IgI and the acid box exhibited higher binding affinity for FGF and heparin (56). This also agreed with our results indicating that FGFR3⌬AB requires lower concentrations of heparin compared with FGFR3.…”
Section: Gene Expression and Biological Roles Of Fgfrs Insupporting
confidence: 83%
See 1 more Smart Citation
“…Binding of heparin to the canyon stabilizes the dimeric structure of the FGF⅐FGFR complex. This hypothesis is consistent with the results of previous studies demonstrating that FGFR1 lacking IgI and the acid box exhibited higher binding affinity for FGF and heparin (56). This also agreed with our results indicating that FGFR3⌬AB requires lower concentrations of heparin compared with FGFR3.…”
Section: Gene Expression and Biological Roles Of Fgfrs Insupporting
confidence: 83%
“…The mitogenic responses of FGFR3⌬AB to FGF2 and other FGFs in our study were similar to those of the chimeric receptor. Many studies have suggested that the ligand binding domains reside in IgII and IgIII but do not include the acid box (8,56,57). The increased responsiveness of FGFR3⌬AB to FGF2 may be due to a conformational change caused by the complete deletion of the acid box, because the protein folding of the ligand binding region in FGFR3 may be strongly affected by the presence of the acid box.…”
Section: Gene Expression and Biological Roles Of Fgfrs Inmentioning
confidence: 99%
“…The skipping of the a-exon is most drastic in the most aggressive glioma, glioblastoma multiforme (GBM). The FGFR1b isoform has higher affinity for FGF1, a feature that might contribute to tumor growth (Wang et al 1995). The inclusion of the a-exon was shown to be repressed by PTB, which is overexpressed in GBMs (Jin et al 2003).…”
Section: Fgfrsmentioning
confidence: 99%
“…The extracellular region of FGFRs prototypically consists of three immunoglobulin-like domains, a short motif of acidic amino acids (the "acidic box") located just distal to Ig-like domain I, and a heparin binding domain also interposed between the first and second Ig-like domains; however, alternative RNA splicing can result in several isoforms of an FGFR from the one respective gene that differ in their extracellular sequence and possess unique ligand binding properties (14). One such splicing event results in a deletion of the exon encoding the amino-terminal Ig-like domain (domain I), resulting in a shorter, two-Ig-like domain isoform of the receptor (15); such shorter FGFRs ("␤-forms") frequently have higher affinities for some FGFs than do the corresponding longer three-Ig-like domain FGFRs ("␣-forms") and, in some instances, have been associated with tumor progression (16). Another splicing event that can dramatically alter the FGF binding ability of FGFR-1, -2, and -3 involves the alternate usage of either the "IIIb" or "IIIc" exon to encode the carboxyl-terminal portion of Ig-like domain III (14).…”
mentioning
confidence: 99%